EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS SISWA SMA KELAS XI PADA MATERI KESETIMBANGAN KIMIA - Susi Susi; Elvi Yenti (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This research was instigated by Chemistry subject at Senior High School of YLPI Pekanbaru that was dominated by discussion, question, and answer methods. These methods did not train student ability in the inquiry, it was proven by the low score of student science process skill on Chemical Equilibrium lesson. This research aimed at knowing the effectiveness of Problem Based Learning model toward student science process skill on Chemical Equilibrium lesson. Quasi-experimental method was used in this research with pretest posttest control group design. The samples were the eleventh-grade students of Natural Science 1 as the experimental group and the students of Natural Science 2 as the control group, and each class had 20 students. Test and observation sheet were the instruments of this research. The data of science process skill test were analyzed by using statistical test and to test the hypothesis was using t-test. The calculation result data of the mean difference of both classes showed that the score of tobserved was 8.66 and ttable was 1.69 at 0.05 significant level, so tobserved was higher than ttable. It showed that Alternative hypothesis was accepted, it meant that Problem Based Learning model was effective to be used toward student science process skill on Chemical Equilibrium lesson, and the effectiveness percentage score was 75%.